Evidence-based diagnosis : an introduction to clinical epidemiology - Newman, Thomas B; Kohn, Michael A; Steurer, Martina A (Cambridge University Press, 2020)
The textbook focuses on evidence-based medicine, diagnostic testing and clinical epidemiology.
Cambridge medicine
Keywords: klinické laboratorní techniky; Evidence-Based Medicine; Clinical Laboratory Techniques; klinické zkoušky jako téma; Clinical Trials as Topic; Epidemiology; Biomedical Research; diagnostika; biomedicínský výzkum; medicína založená na důkazech; epidemiologie